ART-HISTORY COMPONENT MUSICAL FILLING IN THE FOCUS OF CINEMA CULTURE - Мельничук, Святослав; Мельничук, Максим (SWorldJournal, 2025)
The article examines aspects of the mutual influence of cinema and musical art, the role of music in the artistic and aesthetic structure of the film. For this purpose, specific features of the musical series in the film are comprehended, acquiring somew